The Effectiveness of Corporate Governance in Constraining Fraud: Evidence from Listed Manufacturing Firms in Indonesia - Wati, Yenny; Anugerah, Rita; Ratnawati, Vince (Universitas Syiah Kuala, 2019)
Objective The purpose of this study is to examine the direct effect of good corporate governance mechanisms on financial statement fraud with earnings management as a mediating variable.Design/methodology This study used secondary data from manufacturing companies listed on the Indonesia Stock Exchange for the 2013-2017 period. The sample was determined using the purposive sampling method and was chosen based on certain considerations or criteria. The data in this study was analyzed using partial least square and performed with WarpPLS 5.0 software.Results The results of this study prove that the mechanism of good corporate governance has a negative effect on financial statement fraud and earnings management. Earnings management can affect the effectiveness of good corporate governance mechanisms on financial statement fraud.Research limitations/implications - This research promotes the need for a company to inspect and maintain the importance of good corporate governance to avoid earnings management and fraud practices. From this research, investors can identify which companies apply good corporate governance in their company activities and systems.